Evaluating Differentiated English Teaching in an Inclusive Classroom at the Elementary School Level - Muttaqin, Dedy Ahsan; Rahman, Lalu Isnaeni (TSAQOFAH, 2025)
This research investigates the application of differentiated instruction methods for teaching English language skills at SDN 1 Dasan Geres, an inclusive elementary school in West Lombok, Indonesia. The research investigated how participants comprehended differentiated instruction implementation within inclusive educational environments while teaching literacy and numeracy skills and developing student character. The research framework of this study combined a qualitative descriptive approach with the CIPP (Context, Input, Process, Product) evaluation model. The research team gathered information through comprehensive interviews with English teachers and by examining documents, including lesson plans and student assignments. Teachers recognized the importance of meeting students' varied needs with a systematic, inclusive educational approach and differentiated teaching methods. Teachers experienced obstacles to effective implementation from limited training programs, insufficient resources, excessive teaching loads, inadequate time availability, and challenges managing oversized classes. The application of differentiated instruction strategies emerged inconsistently across subjects because teachers commonly employed informal assessments to create these methods. Teachers dismantled specific barriers through differentiated instruction, leading to higher student engagement and improved self-esteem and participation. Instruction that centers on each student's unique preparation level and personal interests leads to improved literacy abilities and enhanced positive character qualities among students. Research determined that achieving differentiated educational sustainability demands professional development, sufficient instructional resources, and organizational backing for effective teaching strategies in inclusive primary education settings.